A critical analysis of problem areas in respect of assets of insolvent estates of individuals - Evans, Roger Graham (University of Pretoria, 2009)
The Law of Insolvency in South Africa is regulated by the provisions of the Insolvency Act 24 of 1936, with foundations in our common law, which has been influenced by different legal systems from Western Europe. But currently there is also other legislation affecting the insolvent debtor and the property in the insolvent estate. The courts too have had to formulate rules to govern aspects of insolvency law in South Africa. These variables created problem areas in insolvency law and in respect of the of the policies upon which the insolvency system hinges. The predominant policy in South African insolvency is the collection of the maximum assets of the debtor for the advantage of creditors in insolvent estates. This strict creditor orientated approach created further problem areas in respect of assets in the insolvent estates of individual debtors. If advantage to creditors cannot be shown in an application for the sequestration of a debtor’s estate, a court will refuse to grant that order. This strict policy overshadows policy concerns in respect of assets in insolvent estates, and regarding exemption law in respect of those assets. This has resulted in insolvency law reformers in South Africa missing the bigger picture, namely, that South Africa is a creditor driven developing society. It is conceivable that in the transformed South Africa, and in the present world economic chaos, there will be an escalation of sequestrations of the estates of individual debtors. Bearing this in mind, a reformed insolvency law system must become more debtor friendly. A change in the philosophy is needed in favour of an exemption policy for insolvent estates. Exemption policy must be based on the interest of the debtor and his dependants, his dignity, creditor and third party interests, social welfare, and human rights imperatives within the South African constitutional framework. Exemption policy must be linked to the policy of a “fresh start” for the debtor. The different policies in insolvency however create a conflict of interest among the different stakeholders, particularly regarding the assets in insolvent estates, thereby creating problem areas. In this thesis several problem areas are identified and critically analysed. The position of property included in, and excluded from, individuals’ insolvent estates is investigated from a brief historical perspective, and in a brief comparative survey of the insolvency systems of the United Kingdom and the United States of America. Acute problem areas are critically analysed in detail, and the constitutional impact on property in insolvent estates is considered in a separate chapter. The South African Law Reform Commission’s review of South African insolvency law is critically analysed in a chapter of this thesis, concluding that the Commission’s review is inadequate. This thesis concludes that there is a need to reform the insolvency system in South Africa and proposes a way forward in respect of property included in, and property excluded or exempt from insolvent estates. This thesis states the law to the end of October 2008.
Keywords: Advantage to creditors; Creditor; Debtor; Disposition of property

Contribution à la découverte d'un droit commun patrimonial du couple - Brun-Wauthier, Anne-Sophie (Université Grenoble 2, 2003)
En partant des dispositions du droit positif applicables aux époux et aux personnes vivant en concubinage ou en pacs, l'étude avait pour objet l'élaboration d'un droit commun patrimonial applicable à tous les couples. A cet égard, prendre en considération le modèle du mariage dont les règles relativement à l'entraide dans le couple ont été mûries par des siècles de réflexion s'est rapidement imposé. L'une des difficultés majeures a consisté, dès lors, à distinguer parmi les effets patrimoniaux du mariage, ceux qui participent de l'essence du couple - qui ont alors vocation à s'appliquer par analogie à tout couple - de ceux qui participent de l'essence du mariage - qui doivent par conséquent être réservés aux époux. Dans cette perspective, la démarche a consisté à rechercher, dans un premier temps, l'existence d'un droit commun patrimonial imposant une entraide minimale, puis, dans un second temps, l'existence d'un droit commun patrimonial du couple favorisant une entraide maximale. Starting from the measures of the positive law applicable to married couples and to cohabiting couples or partners in a PACS, the purpose of the study was the development of a patrimonial common law applicable to all couples. In this respect, to take into consideration the model of marriage, whose rules relating to mutual help within the couple have been matured by centuries of reflection, has become obvious. One of the major difficulties consisted therefore in discerning, among the patrimonial effects of marriage, those which participate to the essence of the couple – which have thus a purpose of being applied by analogy to all couples – from those which participate to the essence of marriage – which must consequently be applied only to married couples. At this respect, the reasoning has consisted in looking for, firstly, the existence of a patrimonial common law imposing a minimal mutual help, and then, secondly, the existence of a patrimonial common law favouring a maximal mutual help.
Keywords: Droit civil; France; Patrimoine; Régimes matrimoniaux; Successions et héritages